Business ethics on press freedom: A culture of omitting the truth? - Faiz, Azizul; Diyana, Kamarudin (Penerbit Universiti Malaysia Pahang, 2021)
Press freedom in Malaysia is bound under several regulations and restrictions since 1957 when Malaysia was granted independence. A few media and press laws were also inadvertently inherited from the draconian colonial law or introduced in controlling any extremist actions during emergency periods. They were also used to silence any political rivals. Based on the report compiled by Reporters without Borders (RSF), Malaysia jumped 22 places from 123 to 101 in the World Press Freedom Index in 2020, higher than all of our South East Asian neighbouring countries. The success of Malaysia’s freedom of movement was triggered by the reformation of a few media institutions, laws and practices throughout the year. The enhancement of Malaysian press freedom assisted in the development of the country and led the nation to become more progressive and transparent alongside other developing nations worldwide. This qualitative case study analysed ethical issues concerning business ethics through semi-structured interviews with staffs of the media organization as well as from newspaper articles analysis. The case recorded was then categorized into four different setups. The cases were looked at through different facets discussing in detail pertaining to ethical principles and motivation behind the reasonings and actions.